2008
DOI: 10.1080/17450390802027486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of dietary particle fractions on fermentation profile and concentration of microbiota in the rumen of dairy cows fed grass silage-based diets

Abstract: The study evaluated the effects of three different theoretical particle lengths (TPL) of grass silage on the distribution of particle fractions of the diet and the resulting effects on fermentation profile and concentrations of protozoa and mixed bacterial mass in the rumen of three lactating Holstein cows fed total mixed rations (45% grass silage, 5% grass hay and 50% concentrate) ad libitum. Decreasing TPL of grass silage (long, medium, short) reduced particles retained on the 19-mm sieve of the Penn State P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Mean, minimum, and maximum values and CV are presented for each type of microorganisms for each AA in Table 2. The CV of the FAB fraction were the highest for Cys, His, and Met, which also was observed Meyer et al, 1967;Ibrahim and Ingalls, 1972;Williams and Dinusson, 1973;Burris et al, 1974;Rooke et al, 1984;Hvelplund, 1986;Rahnema and Theurer, 1986;Cecava et al, 1988;Erasmus et al, 1994;Cozzi et al, 1995;Ludden and Cecava, 1995;Martin et al, 1996;Ludden and Kerley, 1997;Mabjeesh et al, 1997;Volden and Harstad, 1998;Elizalde et al, 1999;Volden et al, 1999;Korhonen et al, 2002;Robinson et al, 2002;Reynal et al, 2003;Zebeli et al, 2008;Fonseca et al, 2014.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Mean, minimum, and maximum values and CV are presented for each type of microorganisms for each AA in Table 2. The CV of the FAB fraction were the highest for Cys, His, and Met, which also was observed Meyer et al, 1967;Ibrahim and Ingalls, 1972;Williams and Dinusson, 1973;Burris et al, 1974;Rooke et al, 1984;Hvelplund, 1986;Rahnema and Theurer, 1986;Cecava et al, 1988;Erasmus et al, 1994;Cozzi et al, 1995;Ludden and Cecava, 1995;Martin et al, 1996;Ludden and Kerley, 1997;Mabjeesh et al, 1997;Volden and Harstad, 1998;Elizalde et al, 1999;Volden et al, 1999;Korhonen et al, 2002;Robinson et al, 2002;Reynal et al, 2003;Zebeli et al, 2008;Fonseca et al, 2014.…”
Section: Resultssupporting
confidence: 56%
“…2 Data from Martin et al, 1996;Volden and Harstad, 1998;Volden et al, 1999;Korhonen et al, 2002;Reynal et al, 2003;Zebeli et al, 2008;Fonseca et al, 2014. 3 Data from Williams and Dinusson, 1973;Rahnema and Theurer, 1986;Martin et al, 1996;Volden et al, 1999;Shabi et al, 2000;Korhonen et al, 2002;Reynal et al, 2003;Jensen et al, 2006.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data from our research as well as research of other teams have demonstrated that fine chopping of roughage to a theoretical PS of 4 to 6 mm adversely affected rumination activity and rumen fermentation in diets containing relatively large amounts of concentrate (50 to 60% DM). This was equally true for corn silage Yang and Beauchemin, 2006a;Zebeli et al, 2008b), grass silage (Zebeli et al, , 2008c, or silages based on alfalfa or barley (Teimouri Yansari et al, 2004;Yang and Beauchemin, 2007;Alamouti et al, 2009). Studies also showed that a decreased ruminal pH largely contributed to the depression of fiber degradation as well as feed efficiency of the cows (Allen and Mertens, 1988;Krajcarski-Hunt et al, 2002;Zebeli et al, 2010).…”
Section: Forage Particle Sizementioning
confidence: 93%
“…Compared with FRL, however, PARL has been shown to have greater (by up to 50 mmol/L) SCFA and greater amino acid N concentrations, higher fibrolytic bacteria and protozoa counts, but much lower HCO 3 − concentration, lower butyrate proportions, and a pH approximately 0.7 units lower than that of the FRL (Tafaj et al, 2004;Ölschläger, 2007;Zebeli et al, 2008d). Interestingly, the diet-induced changes in the chemical composition of the digesta, in particular the effects of concentrate level, were more pronounced in PARL than in FRL Zebeli et al, 2008c). The latter was explained by greater microbial density and diversity of PARL (Ölschläger, 2007).…”
Section: Differences Between Rumen Digesta Phasesmentioning
confidence: 98%
See 1 more Smart Citation